The interface effect - Galloway, Alexander R.
The Interface Effect fuses sophisticated contemporary theory with a detailed knowledge of the technics and techniques of digital media. Galloway is an important voice, and the book is sure to have a wide uptake among those interested in new media theory and contemporary aesthetics." Jodi Dean, author of Blog Theory: Feedback and Capture in the Circuits of Drive "Employing a sustained, powerful methodology, The Interface Effect sparkles with original insights. Galloway is interested not only in the effects that interfaces have, but also in them as themselves the results of cultural, technological, economic, and political forces. This double movement provides a way to connect the historical with the political, and the technological with both. This book is essential reading for anyone interested in new media studies, contemporary theory, and digital technologies." N. Katherine Hayles, Professor of Literature, Duke University, and author of How We Think: Digital Media and Contemporary Technogenesis